Selected Natural Stimulants in Food and Their Effects on Human Health - Jany, Natalia; Lesiów, Tomasz (Wybrane naturalne substancje pobudzające w żywności i ich wpływ na zdrowie człowieka, 2023)
The paper discusses the various stimulants found in foods and the prevalence and public knowledge of their effects on health. The study aimed to identify the impact of consuming selected natural stimulants on human health. A survey was conducted online in 2023, based on the authors’ questionnaire, among people of different ages and education. Stimulants were found to be commonly used by the survey respondents. A significant number of the respondents consumed stimulants even several times a day (41.1%), however they were aware of the adverse effects of consuming these substances and many expressed a desire to reduce their consumption (46.1%). A total of 84.1% indicated the need for more education on the subject, noting that the information they gained from the Internet regarding both the effects and safe doses of a substance was insufficient.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2023, Nr 39, s. 84-95
Keywords: caffeine; health; food; kofeina; zdrowie; żywność